2006
DOI: 10.1248/bpb.29.1767
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effect of Extracts from Ginkgo biloba Leaves in Behavioral Models

Abstract: In recent years, depression has become recognized as a major public health problem. It is estimated that in the US approximately 20% of the population has some depressive symptoms, and around 2-5% are thought to suffer from severe forms of depression.1) Understanding how to prevent and treat depression is therefore an urgent subject. Although the mechanism provoking depression has not been clearly elucidated, the main trigger is known to be exposure to chronic stress.2,3) Many types of antidepressant drugs suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 35 publications
3
38
0
4
Order By: Relevance
“…The other dosages we tested (15,150 and 500 mg/kg) did not affect the duration of immobility. Such a U-shaped activity curve has been reported for some herbal medicines, 10,11,18) although the reason for this has not been clarified. Psychostimulants, which exert an indiscriminate motor stimulating activity, have previously been shown to have efficacy at decreasing immobility in FST, but no antidepressant activity.…”
Section: Discussionmentioning
confidence: 89%
“…The other dosages we tested (15,150 and 500 mg/kg) did not affect the duration of immobility. Such a U-shaped activity curve has been reported for some herbal medicines, 10,11,18) although the reason for this has not been clarified. Psychostimulants, which exert an indiscriminate motor stimulating activity, have previously been shown to have efficacy at decreasing immobility in FST, but no antidepressant activity.…”
Section: Discussionmentioning
confidence: 89%
“…Such a U-shaped activity curve has been reported for some herbal medicines. [16][17][18] Although the reasons have not been clarified, we considered that higher dosage of genistein, such as 100 mg/kg, might exert detrimental effects 19) and thus diminish the antidepressant-like effect.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the effect of the aqueous macerate of G. dalenii could be also mediated through the interaction of the aqueous macerate of G. dalenii with serotoninergic/ noradrenergic systems or NMDA system, as previously demonstrated (Trullas& Skolnick The phytochemical characterization of the aqueous macerate of G. dalenii in this study revealed the presence of flavonoids, saponins, tannins and polyphenols. This finding, coupled with recent studies showing that extract containing flavonoids have antidepressant activity in mice in both the FST and TST (Zhang, 2004;Sakakibara et al, 2006), suggests that the antidepressant effects of the aqueous macerate of G. dalenii might be related to the presence of flavonoids.…”
Section: Discussionmentioning
confidence: 53%